Contextualizing corruption: A cross-disciplinary approach to studying corruption in organizations - Kanti Pertiwi (Administrative Sciences, 2018)
This paper aims to establish how organization and management research, an extensive field that has contributed a great deal to research on corruption, could apply insights from other disciplines in order to advance the understanding of corruption, often considered as a form of unethical behavior in organizations. It offers an analysis of important contributions of corruption research, taking a 'rationalist perspective', and highlights the central tensions and debates within this vast body of literatures. It then shows how these debates can be addressed by applying insights from corruption studies, adopting anthropological lens. The paper thus proposes a cross-disciplinary approach, which focuses on studying corruption by looking at what it means to individuals implicated by the phenomenon while engaging in social relations and situated in different contexts. It also offers an alternative approach to the study of corruption amidst claims that anti-corruption efforts have failed to achieve desirable results.
Keywords: 350; organizational corruption; business ethics; management; governance